Report of the Committee on Key Villages - Planning Commission (Planning Commission, 1959)
India possesses over 200 million cattle and buffaloes, i.e., about a quarter of the world’s bovine population. Notwithstanding this there is extreme shortage of milk, the major source of animal protein in the diet of human beings in this country. The working efficiency of bullocks, on which the entire agricultural economy of the country depends, is also low. Of t he total cattle, 47-25 million are about cows and 21-07 million buffaloes, which arc kept for breeding or milk production. The total annual milk product ion in the country is estimated at 477 million , which works out at about 5 or,. per capita per day as against the 10 ozs. considered essential by nutritionists for a balanced diet.
Ministry of Food and Agriculture (Department of Agriculture) Government of India
Ministry of Food and Agriculture (Department of Agriculture) Government of India